A combinatorial coordination-modulated approach to all-hydrocarbon-ligated intermetallic clusters. Issue 27 (15th March 2022) - Heiß, Patricia; Hornung, Julius; Gemel, Christian; Fischer, Roland A.
Abstract : We introduces a new concept for experimental design of cluster growth investigation in the Ni(cod)2 /ECp* (E = Al, Ga) system with 3-hexyne as a coordination modulator by in situ analysis of cluster mixtures combined with theoretical modelling. Abstract : The formation of Hume-Rothery-inspired intermetallic and all-hydrocarbon-ligated Ni/E clusters (E = Al, Ga) is studied. A library of organo-metallic complexes and small clusters is obtained when [Ni(cod)2 ] is treated with ECp* in the presence of 3-hexyne (hex). While the alkyne reversibly coordinates side-on to the Ni/Ga species, it dimerizes at the Ni/Al species. The mass spectrometric monitoring of the reaction solutions provides insight into the chemical complexity generated by a combinatorial, coordination-modulated approach to control cluster nucleation and growth aiming at cluster size-focusing and selective synthesis of species such as [Ni4 Ga4 ](Cp*)4 (hex)2 .